An exclusion map of Marfan syndrome. Issue 2 (February 1990) - Blanton, S H; Sarfarazi, M; Eiberg, H; de Groote, J; Farndon, P A; Kilpatrick, M W; Child, A H; Pope, F M; Peltonen, L; Francomano, C A
Abstract : The combined genetic data between the Marfan syndrome and 75 informative loci on 18 autosomes were used to construct an exclusion map for this disorder. Data are also presented for a further two unmapped markers. The most likely location of the Marfan syndrome gene is highlighted and all the unexcluded areas of the genome are displayed in a graphical form. This exclusion map shows that almost 75% of the genome has been excluded as a likely location for the Marfan syndrome gene in the majority of the families studied. Apart from chromosomes 8, 13, 21, and 22, for which no data were available, other regions not excluded yet include 5p, 6p, 9p, 10p, 12p, 15, 17p, 18, and 20p. Future linkage analysis using markers located in the highlighted regions should facilitate the identification of the site of the Marfan syndrome gene.